2020
DOI: 10.7759/cureus.8597
|View full text |Cite
|
Sign up to set email alerts
|

A Workshop to Reflect on Personal Resilience in Emergency Medicine Residents: Applying the Connor-Davidson Resilience Scale, Visual Explorer, and the Critical Incident Questionnaire to Support Introspection

Abstract: Burnout among emergency medicine (EM) residents is gaining increasing attention. The authors designed a workshop to assess EM residents' resilience using a validated scale to prompt personal reflection. The workshop then shifted to peer-to-peer conversations and sharing using images from Visual Explorer (VE) to further reflect on resilience. Overall, resident resilience scores were below those of the US general population, with postgraduate year (PGY)-2 year residents having the lowest scores. The workshop was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
2
1
Order By: Relevance
“…A US study using Explorer for emergency medicine residents reported an average CD-RISC score of 76.5, which is lower than the average scores of healthy adults in the US. [17] While the CD-RISC scores of the general Korean population are lower than those of the general US population owing to cultural differences, the average post-EFAT score in this study was higher than that of the general Korean population. In addition, given that our study and Kim et al's [27] study were conducted during the COVID-19 pandemic, whereas the aforementioned studies were conducted before the pandemic, it is necessary to follow up on the resilience levels of EPs after the pandemic ends.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…A US study using Explorer for emergency medicine residents reported an average CD-RISC score of 76.5, which is lower than the average scores of healthy adults in the US. [17] While the CD-RISC scores of the general Korean population are lower than those of the general US population owing to cultural differences, the average post-EFAT score in this study was higher than that of the general Korean population. In addition, given that our study and Kim et al's [27] study were conducted during the COVID-19 pandemic, whereas the aforementioned studies were conducted before the pandemic, it is necessary to follow up on the resilience levels of EPs after the pandemic ends.…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, residents' wellbeing and their relationships with colleagues showed improvements. [16] In O'Connell et al [17] assessment of a resilience workshop that facilitated reflection, collaboration, and communication among emergency medicine residents, participants reported satisfaction with sharing their experiences of feeling resilient with their peers.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The relationship between critical incidents and burnout has been studied among various health professions and has been evaluated in a broad set of specialties such as anesthesia, emergency medicine, obstetrics and gynecology, and pediatric hematology/oncology. [12][13][14][15][16][17] However, to our knowledge, critical incident reports have not been analyzed in surgical subspecialties. Negative experiences, in particular, have an adverse effect on resident wellness by contributing to stress and burnout.…”
mentioning
confidence: 99%